PELATIHAN PENGGUNAAN APLIKASI MACROMEDIA FLASH SEBAGAI MEDIA PEMBELAJARAN INOVATIF PADA CALON GURU SEKOLAH DASAR NEGERI 20 KURAO PAGANG - Sakinah, Fitri; Fitria, Yanti; Darmansyah, Darmansyah (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This community service program was designed to improve the teaching skills of prospective educators and teachers of SDN 20 Kurao Pagang in Padang City through the use of interactive learning media based on Macromedia Flash. This activity, which took the form of training and workshops, was attended by 10 teachers from the primary school. There were three phases in this program: the first phase involved socialization which included observation and interview with the principal, the second phase was training and mentoring, and the third phase was evaluation. The results of this program showed that out of 10 teachers, 8 teachers (83.33%) successfully created interactive learning media using Macromedia Flash, while the other 4 teachers (10%) experienced difficulties, which may be due to their first experience using Macromedia Flash software in the creation of learning media.